Assessment and prediction of tablet properties using transmission and backscattering Raman spectroscopy and transmission NIR spectroscopy - Elisabeth Peeters; Ana Filipa Tavares da Silva; Maunu Toiviainen; Jeroen Van Renterghem; Jurgen Vercruysse; Mikko Juuti; Joao Almeida Lopes; Thomas De Beer; Chris Vervaet; Jean-Paul Remon (Elsevier, 2016)
This study investigated whether Raman and Near Infrared (NIR) spectroscopy could predict tablet properties. Granules were produced on a continuous line by varying granulation parameters. Tableting process parameters were adjusted to obtain uniform tablet weight and thickness. Spectra were collected offline and tablet properties determined with traditional analyzing methods. Partial Least Squares (PLS) regression was used to correlate spectral information to tablet properties, but predictive models couldn't be established. Principal component analysis (PCA) was effectively used to distinguish theophylline concentrations and hydration levels and multiple linear regression (MLR) analysis allowed insight on how granulation parameters affect granule and tablet properties.